Vitamin D Deficiency in Children With Vasovagal Syncope Is Associated With Impaired Circadian Rhythm of Blood Pressure - Zou, Runmei; Wang, Shuo; Cai, Hong; Li, Fang; Lin, Ping; Wang, Yuwen; Wang, Cheng (Frontiers in Neuroscience, 2021)
Background: Vitamin D plays an important role in regulating the cardiovascular system. We aimed to explore the serum vitamin D level in pediatric patients with vasovagal syncope (VVS) and compare the clinical characteristics of VVS children with vitamin D deficiency and sufficiency. Methods: This was a retrospective study. 130 syncopal children diagnosed with VVS were included in the study. 110 age and gender matched healthy individuals were enrolled as control. According to serum 25(OH)D level, VVS patients were divided into vitamin D sufficient group and vitamin D deficient group. Detailed information on demographic data, baseline laboratory testing, echocardiogram, ambulatory blood pressure monitoring, and Holter ECG recording were extracted. Results: VVS children had a higher incidence of vitamin D deficiency compared with healthy individuals (33.8% vs 20.0%, P=0.017). VVS patients with vitamin D deficiency had a higher rate of non-dipper blood pressure (79.5% vs 59.3%, P=0.021) and a lower value of rMSSD (median 107.8 vs 141.0 ms, P=0.035) compared with those with vitamin D sufficiency. Multivariate regression analysis showed that non-dipper blood pressure was associated with serum 25(OH)D level [OR=0.979, 95%CI (0.960, 0.999), P=0.036]. Conclusions: VVS pediatric patients had a higher incidence of vitamin D deficiency. Vitamin D deficiency is associated with non-dipper blood pressure, suggesting that vitamin D deficiency impairs the circadian rhythm of blood pressure in VVS pediatric patients.